Crash - McMann, Lisa (New York : Simon Pulse, 2013)
Sixteen-year-old Jules, whose family owns an Italian restaurant and has a history of mental illness, starts seeing a recurring vision about a rival restaurant, a truck crash, and forbidden love.
Keywords: Visions -- Juvenile fiction; Mentally ill -- Juvenile fiction; Teenage girls -- Juvenile fiction; Paranormal fiction; Love stories; Families -- Juvenile fiction; Restaurants -- Juvenile fiction; Visions -- Fiction; Mentally ill -- Fiction; Teenage girls -- Fiction; Supernatural -- Fiction; Love -- Fiction; Family life -- Fiction; Restaurants -- Fiction